The Application of AI and Computer Science in the Context of International Law and Governance "Opportunities and Challenges" - Ness, Stephanie; Singh, Navdeep; Volkivskyi, Mykola; Phia, Wong Jest (American Journal of Computing and Engineering, 2024)
Purpose: The purpose of "Governing Artificial Intelligence: Ethical, Legal, and Technical Opportunities and Challenges" is to examine the impact of artificial intelligence (AI) on various societal aspects and to underscore its potential benefits for human rights, social welfare, and economic growth. The essay emphasizes the necessity of regulating AI systems in a fair, transparent, and responsible manner, especially in high-risk sectors. Materials and Methods: Research Design: The essay employs a literature review and analysis approach to explore the ethical, legal, and technical challenges associated with governing AI. Method of Data Collection: Data collection primarily involves gathering information from existing literature, reports, and expert opinions. Analysis and Presentation: The data is analyzed qualitatively to provide insights into the complexities of AI governance. The findings are presented systematically to address different dimensions of the topic. Findings: The essay presents a comprehensive analysis of the ethical, legal-regulatory, and technological challenges in governing AI. It highlights the need for robust governance frameworks to ensure the responsible development and deployment of AI systems. Implication to Theory, Practice, and Policy: The study is informed by various theories on ethics, governance, and technology. Validation of these theories is achieved through a critical examination of existing literature and empirical evidence. Practitioners are recommended to adopt principles of fairness, transparency, and accountability in the development and deployment of AI systems. Additionally, continuous monitoring and evaluation mechanisms should be established to ensure compliance with ethical standards. Policymakers are encouraged to enact regulations that promote the ethical and responsible use of AI technologies. This includes establishing clear guidelines for AI development, deployment, and accountability mechanisms to address potential risks and ensure societal well-being.